A Special Study Institute Program - New York State Education Dept., Albany. Div. for Handicapped Children; New York State Education Dept., Albany. Div. for Handicapped Children; Rockland County Board of Cooperative Educational Services, West Nyack, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Described is an institute with the stated purpose of acquainting public school administrators with the role of the special education administrator and to present a general overview of special education programs and issues. The stated objectives of the institute held are introduction to general education administrators of the current issues in special education in New York State and nationwide and sensitization to everyday problems of special education administrators. The Special Education Administration Task Simulation Game, which was used at the institute as the major educational tool, is described to provide a standardized experience which a group of educators can experience in common and then compare various approaches to coping with daily problems typically confronting the administrator. An evaluation after the institute indicated that 75% of the participants rated the value of the workshop as most worthwhile, and simulation was found to be preferable to other training methods by the participants. (CB)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Div. of Handicapped Children and Youth.
ERIC Note: Reprint of Proceedings of Special Study Institute, December 2-4, 1971, Nanuet, New York.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administration; Administrative Policy; Administrative Problems; Administrator Role; Exceptional Child Education; Handicapped Children; Institutes (Training Programs); Supervision